IDNLearn.com connects you with experts who provide accurate and reliable answers. Ask your questions and receive reliable, detailed answers from our dedicated community of experts.
Sagot :
Answer:
[tex]f^{-1}(x) = \sqrt[3]{\frac{x -4}{5}} +2[/tex]
Step-by-step explanation:
Given
[tex]f(x) = 5(x - 2)^3 + 4[/tex]
Required
Determine the inverse
[tex]f(x) = 5(x - 2)^3 + 4[/tex]
Replace f(x) with y
[tex]y = 5(x - 2)^3 + 4[/tex]
Swap the positions of x and y
[tex]x = 5(y - 2)^3 + 4[/tex]
Make y the subject
[tex]x -4= 5(y - 2)^3[/tex]
Divide by 5
[tex]\frac{x -4}{5}= (y - 2)^3[/tex]
Take cube roots of both sides
[tex]\sqrt[3]{\frac{x -4}{5}}= y - 2[/tex]
Add 2 to both sides
[tex]\sqrt[3]{\frac{x -4}{5}} +2 = y[/tex]
[tex]y = \sqrt[3]{\frac{x -4}{5}} +2[/tex]
Replace y with [tex]f^{-1}(x)[/tex]
[tex]f^{-1}(x) = \sqrt[3]{\frac{x -4}{5}} +2[/tex]
We appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. IDNLearn.com is your source for precise answers. Thank you for visiting, and we look forward to helping you again soon.